The varieties of faith-related agencies - Smith, Steven Rathgeb; Sosin, Michael R. (2001)
Although some recent literature suggests religious social service agencies can help governments reach important social program goals, the true social organization and services of the agencies remain in dispute. This article interviews officials in the wide class of "faith-related" agencies in two cities to consider two aspects of this issue: the ties or "coupling" of agencies to faith, and the impact of coupling on agency structure and service programming. The results suggest that many sampled agencies are loosely tied to faith in terms of resources, more tightly coupled in terms of authority, and moderately coupled with respect to culture; that certain aspects of service-delivery technology are heavily secularized in many agencies; that faith is more influential in such matters as the agencies' choices of services; and that the larger, potentially more secularized agencies that might be least likely to be characterized as faith based balance differing sets of resources and thereby can more fully deliver services that arguably express faith in action. Given this finding and that most agencies profess a focus on protecting the dignity and rights of clients rather than on individual responsibility or other themes that are stressed by some recent policy proposals, governments need to be extremely selective in funding agencies to promote those proposals' themes. - Reproduced
Keywords: Social services; Nongovernmental organizations